FORMULASI DAN UJI EFEKTIVITAS SEDIAAN GEL DARI EKSTRAK DAUN SUJI (Dracaena agustifolia) PADA TIKUS JANTAN PUTIH SEBAGAI ANTIINFLAMASI - Delisma Marsauli Simorangkir; Linta Meliala (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Background: Leaf suji (Dracaena angustifolia) is a native plant of Indonesia that is used as a natural food coloring. However, ethnobotany and pharmacologicalreviews reveaed that this plant had potential as amedicinal ingredient one of them is for anti-inflamatory because it contains saponins that can reduce swelling. Methods: The objective of thE study to determine the gel from suji leaf extract works effectively as an anti-inflmatory against the feet of white male rays and to determine at what concentration the gel preparation from suji leaf ekstract is good as an anti-inflamatory. The method of the study used experimental. The results of the study: The gel preparation of suji leaf extract works effectively as an anti- inflamatory because it can inhibit inflamation in the feet of male white wistar rats well and the concentration of carrageenan induction, which is at a concentration of 20%. Keyword : Gel preparation, daun suji, anti-inflamatory